PENGARUH PERUBAHAN SUHU TERHADAP UJI IMPAK LAPISAN NIKEL-KROM PADA SUBSTRAT TEMBAGA - Ahzan, Sukainil; Ahmadi, Ahmadi (Lensa : Jurnal Kependidikan Fisika, 2015)
It has been done plating a copper with process electroplating technique using a solution of nickel and chrome. The purpose of this study to find the best strength of the layer with the optimal flow. The strength of the material in the test with the impact test on a sample of coated copper at different work flows (1A, 1.5 A, 2.0 A, and 2.5 A). The results of the impact energy impact test obtained for each flow which is 2.1566 J / mm2; 2.3017 J / mm2; 1.9319 J / mm2; 1.9205 J / mm2. From the analysis concluded layer with high impact strength at an operating current of 1.5 A